Posttraumatic Growth After MDMA‐Assisted Psychotherapy for Posttraumatic Stress Disorder - Gorman, Ingmar; Belser, Alexander B.; Jerome, Lisa; Hennigan, Colin; Shechet, Ben; Hamilton, Scott; Yazar‐Klosinski, Berra; Emerson, Amy; Feduccia, Allison A. (Journal of traumatic stress, 2020)
3,4‐Methylenedioxymethamphetamine (MDMA)–assisted psychotherapy for posttraumatic stress disorder (PTSD) has been shown to significantly reduce clinical symptomatology, but posttraumatic growth (PTG), which consists of positive changes in self‐perception, interpersonal relationships, or philosophy of life, has not been studied with this treatment. Participant data (n = 60) were pooled from three Phase 2 clinical studies employing triple‐blind crossover designs. Participants were required to meet DSM‐IV‐R criteria for PTSD with a score higher than 50 on the Clinician‐Administered PTSD Scale (CAPS‐IV) as well as previous inadequate response to pharmacological and/or psychotherapeutic treatment. Data were aggregated into two groups: an active MDMA dose group (75–125 mg of MDMA; n = 45) or placebo/active control (0–40 mg of MDMA; n = 15). Measures included the Posttraumatic Growth Inventory (PTGI) and the CAPS‐IV, which were administered at baseline, primary endpoint, treatment exit, and 12‐month follow‐up. At primary endpoint, the MDMA group demonstrated more PTG, Hedges’ g = 1.14, 95% CI [0.49, 1.78], p < .001; and a larger reduction in PTSD symptom severity, Hedges’ g = 0.88, 95% CI [−0.28, 1.50], p < .001, relative to the control group. Relative to baseline, at the 12‐month follow‐up, within‐subject PTG was higher, p < .001; PTSD symptom severity scores were lower, p < .001; and two‐thirds of participants (67.2%) no longer met criteria for PTSD. MDMA‐assisted psychotherapy for PTSD resulted in PTG and clinical symptom reductions of large‐magnitude effect sizes. Results suggest that PTG may provide a new mechanism of action warranting further study.